The house at Pooh Corner - Milne, A. A. (Alan Alexander), 1882-1956.; Shepard, Ernest H. (Ernest Howard), 1879-1976. (New York : Puffin, 1992)
Ten adventures of Pooh, Eeyore, Tigger, Piglet, Owl, and other friends of Christopher Robin.
830
Accelerated Reader AR
Keywords: Fairy tales; Toys -- Fiction